P134 Sensitisation To Cross-reactive Carbohydrate Determinants In Britain's Bakers: The Implications For Health Surveillance. (10th November 2014) - Harrison, H; Welch, J; Schofield, S; Cannon, J; Fitzgerald, B; Jones, M
Abstract : Introduction and objectives: The diagnosis of baker's asthma as part of health surveillance schemes in some UK supermarkets relies on determining sensitisation to wheat flour and/or alpha amylase. Recently, data have emerged suggesting that serum IgE analysis in bakers may be complicated by the presence of clinically irrelevant specific IgE to cross-reactive carbohydrate determinants (CCDs), which are complex-type Asn (N)-linked glycan structures commonly formed in plants. Potentially this might lead to false positive flour specific IgE assays, which would have an impact on bakers undergoing surveillance. The aim of this study was to identify the prevalence of CCD sensitisation in UK bakers and investigate the impact of CCD specific IgE within a health surveillance setting. Methods: Serum samples from UK bakers attending our occupational asthma clinic (n = 209) were analysed for specific IgE to CCD (MUXF 3 ) using ImmunoCAP assay (Phadia). Any positive samples were further tested for specific IgE to grass pollen, and competitive inhibition assays were used to determine cross-reactivity between CCD, flour and grass pollen. Results: Sensitisation rates to CCD in our population of UK bakers were low (7%) despite high sensitisation rates to grass pollen (48%) and flour (60%). Sensitisation to CCD was more prevalent in those sensitised to either flour or grass than in those not sensitised to flour (11.5% vs 0%, p < 0.001) or grass (10.9% vs 2.8%, p = 0.025). We observed cross reactivity between flour and grass pollen and competitive inhibition assays between CCD and flour or grass pollen revealed cross-reactivity in some but not all sensitised bakers. Conclusions: Our study demonstrated that a minority of bakers were sensitised to CCD and, interestingly, this was associated with being co-sensitised with both flour and grass. It is unlikely that CCDs have major implications for the health surveillance for UK bakeries. In the minority of bakers with CCD specific IgE, there was some suggestion that CCDs may play a role in the cross-reactivity between flour and grass pollen, although in others it was less likely. Within the clinical setting, it may be prudent to measure CCD specific IgE in bakers who are co-sensitised to both flour and grass pollen.